Dr. Adam Lowenstein — Deep Plane Facelift — Santa Barbara - Lowenstein, Adam (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Adam Lowenstein, practicing in Santa Barbara, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003277; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; santa barbara